2018
DOI: 10.1111/jcpe.13016
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and risk of Alzheimer′s disease, mild cognitive impairment and subjective cognitive decline: A case–control study

Abstract: Aims To test the hypothesis that periodontal disease contributes to increased risk of mild cognitive impairment (MCI), subjective cognitive decline (SCD) and Alzheimer′s disease (AD). Materials and methods This case–control study was conducted over a 3‐year period in the municipality of Huddinge, Sweden. In total, 154 cases were consecutively enrolled from the Karolinska Memory Clinic at the Karolinska University Hospital and allotted to three diagnostic groups: AD, MCI and SCD, collectively referred to as “ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(168 citation statements)
references
References 44 publications
2
160
0
6
Order By: Relevance
“…Recently, some reports have focused on possible association among oral health‐related factors, such as periodontal disease and tooth loss, and Alzheimer's disease progression . Although some clinical and molecular studies have reported on these statistical associations, causative relationships have not been demonstrated . A recent study, however, have done an initial step toward proving causative relationship between P. gingivalis infection and Alzheimer's disease, as stated earlier in the Etiology section of the present manuscript …”
Section: Research and Future Directionsmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, some reports have focused on possible association among oral health‐related factors, such as periodontal disease and tooth loss, and Alzheimer's disease progression . Although some clinical and molecular studies have reported on these statistical associations, causative relationships have not been demonstrated . A recent study, however, have done an initial step toward proving causative relationship between P. gingivalis infection and Alzheimer's disease, as stated earlier in the Etiology section of the present manuscript …”
Section: Research and Future Directionsmentioning
confidence: 77%
“…81 Although some clinical and molecular studies have reported on these statistical associations, 82,83 causative relationships have not been demonstrated. 81,83 A recent study, however, have done an initial step toward proving causative relationship between P. gingivalis infection and Alzheimer's disease, as stated earlier in the Etiology section of the present manuscript. 34…”
Section: What Are the Most Promising Strategies?mentioning
confidence: 88%
“…In the last decades, human periodontitis and its ultimate sequel (i.e. tooth loss) have been associated with cognitive decline/impairment in patients with AD (Holmer, Eriksdotter, Schultzberg, Pussinen, & Buhlin, ; Ide et al, ; Takeuchi et al, ). A recent meta‐analysis of observational studies showed that subjects diagnosed with periodontitis have a 1.6‐fold increased risk of developing AD (Leira et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study showed that severe periodontitis was an independent predictor for early-onset poststroke depression status [6]. A case-control study demonstrated that mild cognitive impairment, subjective cognitive decline, and AD were associated with increased numbers of deep periodontal pockets (OR = 8.43; 95% CI = 4.00-17.76) [26]. A cohort study reported that patients with 10 years of chronic periodontitis exposure had a higher risk of developing AD than the unexposed groups (adjusted hazard ratio [aHR] = 1.707; 95% CI = 1.152-2.528) [8].…”
Section: Discussionmentioning
confidence: 99%